Effect of high-energy heavy-ion irradiation on electromechanical coupling factor of piezoelectric lead zirconate titanate. (18th February 2021) - Takechi, Seiji; Fujita, Shogo; Konishi, Naoki; Miyachi, Takashi; Kobayashi, Masanori; Okudaira, Osamu; Okada, Nagaya; Fujii, Masayuki; Shibata, Hiromi; Murakami, Takeshi; Uchihori, Yukio
Abstract: The variation of the electromechanical coupling factor of lead zirconate titanate (PZT) was studied using a piezoelectric PZT disk exposed to a 400 MeV/n xenon beam. The resonant and antiresonant frequencies were measured in pairs by an impedance analyzer in situ manner. A systematic behavior of the pairs resulted in a decrease of the coupling factor. It was found that the coupling factor linearly decreased with increasing integrated beam energy incident on the PZT disk while its surface temperature was equilibrium at room temperature. We discuss a possible PZT-based radiation detector for practical use in a high-radiation field.